FACTORS INFLUENCING THE PERFORMANCE OF SUSTAINABLE OIL PALM GROWERS COOPERATIVE IN SABAH - Ainul Shazwin Sahidan; Zaki Aman; Abdul Rahman Abdul Rahim; Nazirah Che Jaafar; Humaira Mat Taib; Rahmahwati Rasuddin; Amran Arifin; Mohd Ridzuan Sohimi, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Almost one million hectares of oil palm in Malaysia have been planted by the oil palm independent smallholders (OPISH). Most of these farms are small size holding and scatters throughout Malaysia. These factors cause them to face several problems and consequently put their income below potential. To assist the OPISH, the government had introduced the oil palm grower cooperative known as Koperasi Penanam Sawit Mampan (KPSM). The objective of KPSM is to increase the oil palm yield, OPISH incomes, and as a platform of interaction between OPISH and extension officers to discuss their problems. However, cooperatives' performance can be influenced by several factors. This paper aims to study the extension officer and members' participation as independent variables. Good governance is incorporated as a moderator variable to investigate a cooperative's performance. The partial least squares (PLS 3.0) and structural equation modelling instruments are used to analyse the data in this study. Most of the respondents are male, and 22% are of the younger generation. The results demonstrated that good governance (p-value of 0.095(p<0.1) and t=1.669 (more than 1.64) has a moderate relationship between members' participation and cooperatives' performance. On the other hand, good governance did not strengthen the relationship between the extension officer and co-operatives performance.